A holistic model for measuring financial reporting quality in Sri Lanka (International Journal of Management and Sustainability, 2025)
High-quality financial reporting ensures that disclosed financial information is reliable, relevant, timely, and unbiased, enabling informed stakeholder decisions. The Qualitative Characteristics (QCs) approach, derived from the Conceptual Framework of Financial Reporting, is widely recognized as the most appropriate method to evaluate Financial Reporting Quality (FRQ). Accordingly, this study develops a context-specific FRQ measurement model based on QCs within the Sri Lankan context. The proposed model integrates fundamental (Relevance, Faithful Representation) and enhancing (Comparability, Verifiability, Timeliness, Understandability) characteristics. Data were collected through a questionnaire survey of 397 Sri Lankan investors with accounting knowledge. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to construct the model, supported by Exploratory and Confirmatory Factor Analyses for validation. Reliability and validity were assessed using indicator reliability, Average Variance Extracted (AVE), Cronbach’s alpha, composite reliability, Fornell–Larcker, and HTMT criteria. All QCs significantly influence FRQ, with relevance and faithful representation identified as primary drivers. The resulting model provides a holistic, IASB-aligned tool for assessing FRQ, supporting stakeholders in evaluating the decision usefulness of financial information. The findings are limited to investors with accounting knowledge, which may constrain generalizability. Future research could extend the model to diverse stakeholder groups.